ANALISIS PENGARUH EARNING PER SHARE DAN DEVIDEN PAYOUT RATIO TERHADAP HARGA SAHAM (STUDI KASUS PADA PERUSAHAAN UNITED TRACTORS TBK) - Yordan, Meiriki; Tigor, Ryan Hasianda; Lestari, Deara Shinta (STIE IBEK Pangkalpinang, 2023)
This research was entitled: “Analisis Pengaruh Earning Per Share dan Deviden Payout Ratio Terhadap Harga Saham (Studi Kasus Pada Perusahaan United Tractors Tbk)”. This study aims to determine the effect of Earning Per Share (EPS) and Dividend Payout Ratio (DPR) on share prices in the United Tractors Tbk company for the 2008-2022 period. This study uses secondary data with the documentation method and processed with the JASP tool to test the multiple linear regression hypothesis. The results showed (1) Earning Per Share has a partial effect on stock prices, a significance value of 0.010 is less than 0.05 and a t count value of 3.039 is greater than a t table value of 2.17881. (2) The dividend payout ratio has no partial effect on stock prices, with a significance value of 0.175 is greater than 0.05 and the t count value is 1.441, which is less than the t table value of 2.17881. (3) Earning Per Share and Dividend Payout Ratio simultaneously influence the significance value of 0.027 which is less than 0.05 and the f count value is 4.970 which is greater than the f table value of 3.89.